Epidemiological and Anatomopathological Characteristics of Breast Tumors in Young Women in Cotonou in the Republic of Benin from 2015 to 2019...... - DANGBEMEY, D. Patrice; Aboubakar, Moufalilou; OGOUDJOBI, OGOURINDÉ MATHIEU; GNANGNON, FREDDY HOUEHANOU RODRIGUE; AZONBAKIN, AZANDÉGBÉ SIMON; TOGNIFODE, Véronique; TSHABU TSHINGUTA ÉPSE AGUEMON, CHRISTIANE; HOUNKPATIN, BENJAMIN IGNACE B.; TONATO EPSE BAGNAN, JOSIANE ANGÉLINA ADJOUA; DENAKPO, Justin Lewis (My University, 2021)
Abstract: Objective: Study the epidemiological and anatomopathological characteristics of breast tumors of young woman. Patients and Methods: This was a retrospective and evaluative cross-sectional study of patients treated for a breast tumor between January 1, 2015 and December 31, 2019 in two hospitals in Cotonou. All the complete files of patients under the age of 40 treated for breast tumors of whatever nature were listed. The patients were recalled for clinical and / or radiological evaluation. The epidemiological and histological characteristics of breast tumors were analyzed. Results: The study involved 231 breast tumors including 12 cancers (5.2%) and 219 benign tumors (94.8%). The mean age of the patients was 25.7 years±7.2. Self-examination was the most common discovery (81%). The average consultation time was 6.4 months. The right breast and the upper-external quadrant were the most affected in 53% and 31.1%, respectively. Fibroadenomas (70.7%) and invasive ductal carcinomas (9/12) were the most frequent. Obesity and a family history of breast cancer were associated with the occurrence of breast cancer in young women (p ≤ 5%). The relative risk of developing breast cancer was practically zero before the age of 30. Benign breast tumors spontaneously regressed in part or in whole in 35.3% of cases (n=55), they were stable in 44.8% of cases (n=70) and increased in volume in 19.8% of cases (n=31). The age of diagnosis strongly influenced the evolution of tumors in the young woman in Cotonou (p=0.02). In 56% of cases, breast tumors diagnosed before the age of 20 spontaneously resolved in part and in whole. The breast cancer case fatality in women under 40 was 11.1%. Conclusion: Breast tumors in young women are mostly benign. More than half of these tumors diagnosed before the age of 20 resolve spontaneously. The risk of breast cancer is virtually zero before the age of 30 in our series.
Keywords: Tumors; Breast; Young Woman; Epidemiology